Chemical composition and diversity of lactic acid bacteria in Guinea grass based silages - Kongsan, S.; Srikijkasemwat, K.; Jirajaroenrat, K.; Suphalucksana, W. (My University, 2019)
Ensilage is considered that widespread among conserving method of fodder crops. The successes of this process depend on bacteria in lactic acid bacteria (LAB) group as existing in forage crops. The chemical composition and diversity of lactic acid bacteria in silages based on guinea grass was investigated. Result showed that the silages contained 62.55 to 76.47% moisture, 23.53 to 37.45% dry matter (DM) and 6.11 to 15.74% ash. Groundnut silage (T3) showed the lowest crude fiber (CF), neutral detergent fiber (NDF) and acid detergent fiber (ADF) contents. Two hundred and eighty-two isolates of LAB were isolated from five silage formula based on guinea grass supplementation with either lead tree leaves or groundnut. Most of isolates were gram-positive and catalase-negative bacteria. Based on morphological characteristics and PCR-RAPD analysis, the isolates were divided into 21 groups (Guinea Grass Mixed Legume Silage (GMLS) 1 to GMLS21). The phylogenetic relation of the representative strains was analyzed from the data of 16S ribosomal DNA sequencing. Prevalent of LAB found in the silages included Lactobacillus plantarum, Pediococcus acidilactici, Pediococcus pentosaceus, Enterococcus hirae, and Weissella paramesenteroides. L. plantarum was a dominant population and found distribution in all silage formula. This study revealed that the silage samples, including guinea grass, lead tree and groundnut contain mainly of L. plantarum. The information obtained can be used for the anterior design of reasonable inoculants for improvement of silage quality for cattle feed.
Keywords: 16S rRNA gene sequence; Lactic acid bacteria; PCR-RAPD; Silage